Factors Which Influence the Effectiveness and Utilization of Computer Based Programs: Implications for Decision-Making - Dave Honeyman (Educational Considerations, 1986)
Student access to computer technology is a financial concern ... the extent to which computers are used after purchase is determined by the enthusiasm of the staff and the support given to them by the administration.